(untitled) (Papeles, 2023)
Within the framework of the research line on the history of the professional field of Social Work in Córdoba that our team has been developing since 2004, we propose to focus on the territories and their social problems from the perspective of oral history and collective memory. In this way, this paper addresses some results of the research project carried out in the biennium 2016-2017 called "Historical reconstruction of neighborhood spaces and their problems, from the memory of the neighbors", in which the presence of the State and other actors in the organizational processes for the resolution of social problems in the Revol, Bella Vista, Observatorio and Alberdi neighborhoods of the city of Córdoba is investigated. The qualitative study combined primary sources -focus groups- and secondary sources -oral history productions of students of the social work career developed during the period 2009-2014 and consultation of bibliography on the object of study-.